Biology of Trichogramma chilonis under varying conditions and their parasitism efficiency in lepidopteran pests - A, ANISHA; O P, RANI (The Indian Journal of Agricultural Sciences, 2024)
The experiment was conducted during 2021 to 2023 at College of Agriculture (Kerala Agricultural University), Vellayani, Thiruvananthapuram, Kerala to evaluate the biology of the egg parasitoid Trichogramma chilonis Ishii under different conditions and its effectiveness in parasitizing lepidopteran pests. Field efficacy of T. chilonis in managing Leucinodes orbonalis Guenee, in brinjal (Solanum melongena L.) cv. Supriya was carried out in randomized block design (RBD) with five treatments (T1, Trichocards @2.5 cc/ha; T2, Trichocards @5 cc/ha; T3, Trichocards @10 cc/ha; T4, Chlorantraniliprole 18.5 sc 0.2 ml/litre, which was the chemical check; and Untreated control) replicated four times. Findings from the study on seasonal biology demonstrated that the developmental period was shortest in summer compared to that in monsoon and winter. Monsoon conditions were more conducive for factors such as sex-ratio, emergence rate and adult longevity, making it the optimal season for its mass production. When Corcyra cephalonica Stainton eggs were stored for varying durations (5, 10, 15 days) under refrigeration, it was observed that the development period of T. chilonis was unaffected. However, adult longevity and sex-ratio gradually decreased with an increase in storage duration, with 10 days being identified as the ideal duration. T. chilonis effectively parasitized eggs of various lepidopteran pests including okra shoot and fruit borer (Earias vittella Fabricius), brinjal shoot and fruit borer (Leucinodes orbonalis Guenee), tobacco cutworm (Spodoptera litura Fabricius), cotton bollworm (Helicoverpa armigera Hubner) and lemon butterfly (Papilio polytes Linnaeus). Field experiments indicated that controlling brinjal shoot and fruit borer infestations was successful by using trichocards at 10 cc/ha in the initial three releases and reducing it to 5 cc/ha. Plots treated with trichocards at 10 cc/ha yielded the highest quantity of marketable fruits, with all treatments proving profitable over the control. Among the different doses of trichocards, the highest dose (10 cc/ha) had the most favourable cost-benefit ratio (1:1.03). The population of natural enemies remained stable across various trichocard doses (42.25–46.25), contrasting with a notable decrease in plots treated with chlorantraniliprole 18.5 sc (23.5).